Fácies, elementos arquiteturais e análise de paleocorrentes da formação Tacaratu: sedimentação Ordovício-Siluriana da sub-bacia de Tucano Norte, Brasil - Santana, Mateus do Nascimento (2024)
The Paleozoic sedimentary record of Northeastern Brazil includes the basal successions of the intracratonic basins of Parnaíba, Araripe, and Tucano-Jatobá, as well as smaller intracratonic basins. Sedimentation during this interval began in the Ordovician from continental-scale alluvial systems that drained the Neoproterozoic orogenic terrains of Gondwana. The Tacaratu Formation represents the basal Paleozoic interval in the Northern Tucano Sub-basin, Northeastern Brazil. This unit is predominantly composed of coarse-grained siliciclastic deposits associated with braided fluvial systems. This study investigates the sedimentary record of the Tacaratu Formation, focusing on facies, facies associations, and paleocurrents. Detailed fieldwork was conducted at 10 localities within the Tacaratu Formation, aiming to analyze facies, deposit geometry, bounding surfaces, and paleocurrents of the unit. Eleven facies were identified, allowing the distinction of four facies associations: FA1 - gravel and sandy bars, FA2 - sandy bars and bar tops, FA3 – coarse-grained middle channel bars, and FA4 - overbank fines. Paleocurrent analysis revealed a predominant northward paleoflow trend, consistent with previous studies, along with local variations suggesting low-sinuosity wandering channel morphologies, previously interpreted as braided. These findings refine the understanding of the sedimentary processes that controlled the deposition of the Tacaratu Formation, offering new insights into the depositional history of early fluvial systems of the Western Gondwana